Desktop encyclopedia of voice and data networking - Muller, Nathan J. (McGraw-Hill, 2000)
A companion volume to the "Desktop Encyclopedia of Telecommunications", this book details the terms and concepts of data communication networks in a manner both in-depth and accessible to beginning professionals.